TRAINING OF TRAINERS FOR CLASS TEACHERS TO IMPROVE STUDENTS ORAL HYGIENE IN MIN 2 KEDIRI - Khafid, Mohammad; Putri, Annisa (Universitas Airlangga, 2024)
Dental caries in Indonesia is a dental health problem that still needs attention. Dental plaque accumulating in the oral cavity can increase the risk of dental caries. To date, brushing your teeth is the most effective effort to remove plaque regularly. It is known that the School Health Program (SHP) has proven effective in increasing students' knowledge, motivation, and skills in brushing their teeth. However, an active role is needed from parents and the school, especially class teachers, to support this SHP program. Therefore, training is needed for class teachers who will later become trainers for students on how to brush their teeth properly and correctly. SHP was carried out on 60 class teachers at Madrasah Ibtidaiyah Negeri (MIN) 2 Kediri in July-August 2023. Participants were given training on how to brushing teeth correctly by the dentists through Focus Group Discussion (FGD) activities and then taught the participants training materials to students in their respective classes for one week. Evaluation of the success of the program was carried out on students one week after the students were taught by their teachers. The result showed that students were able to answer the questionnaire correctly and had optimal oral hygiene. Based on the results, it can be concluded that the training of trainer program on how to brushing teeth for teachers can increase student's knowledge, motivation and ability to maintain oral hygiene.